\(I_g*\)-NORMAL AND \(I_g*\)-REGULAR SPACES - Ravi, O.; Paranjothi, M.; Murugesan, S.; Padmasekaran, S. (Italian Journal of Pure and Applied Mathematics, 2015)
\(I_g^*\)-normal and \(I_g^*\)-regular spaces are introduced and various characterizations and properties are given. Characterizations of normal, mildly normal, g*-normal and regular spaces are also given.